Electrochemical Synthesis of Sm-Co Metal Magnetic Materials by Co-reduction of Sm(III) and Co(II) in LiCl-KCl-SmCl3-CoCl2 Melt. (20th September 2017) - Liu, Yu-Hui; Yan, Yong-De; Zhang, Mi-Lin; Liang, Yuan; Qu, Jia-Miao; Peng-Li,; Ji, De-Bin; Xue, Yun; Jing, Xiao-Yan; Han, Wei
Abstract: High magnetism and magnetization intensity are required for preparing rare-earth-based single-crystal flaky magnetic intermetallic compound materials. Herein, we report high coercivity Sm-Co (Sm2 Co17, SmCo5, Sm2 Co7, SmCo3, and SmCo2 ) intermetallic compounds, which have been synthesized by electrochemical synthesis in LiCl-KCl-SmCl3 -CoCl2 melt. The electrochemical co-reduction behaviors of Sm(III) and Co(II) ions, and the formation of intermetallic compounds in the melt were investigated by cyclic voltammetry (CV), square wave voltammetry (SWV) and open-circuit chronopotentiometry techniques (OCP), respectively. The crystal nature of Sm-Co intermetallic compounds was characterized by X-ray diffraction (XRD), selected area electron diffraction (SAED), high-resolution transmission electron microscopy (HRTEM) and Fast Fourier transform analysis (FFTs) method. At the same time, multilayer planar structure of Sm-Co intermetallic compounds was investigated by transmission electron microscope (TEM) and X-ray photoelectron spectroscopy (XPS). The results showed that as the mass percentage of SmCl3 changed from 0 to 12 wt.%, the phase of Sm-Co intermetallic compounds transferred from Co-rich side to Sm-rich side, and the crystal structures were found to be single-crystal ones. The valence bands and core levels of Sm-Co intermetallic compounds were evolved in the crystal growth process. A structural change in the core levels Sm 3d and Co 2p during the course of transition from pure components to intermetallic compounds occurred, which could be explained by the hybridization of f and d electrons of samarium and cobalt. The results of Sm-Co intermetallic compounds for vibrating sample magnetometer (VSM) test showed that the magnetic densities of Sm2 Co17 and SmCo5 were 157 emu/g and 145 emu/g, respectively.